Adoption of a Holistic Approach to Minimize the Impact of Climate-induced Cardiovascular Diseases - Saurabh RamBihariLal Shrivastava; Prateek Sudhakar Bobhate; Khalid Khan (Research in Cardiovascular Medicine)
Cardiovascular diseases (CVDs) have been acknowledged as a global public health concern owing to their ubiquitous distribution and associated mortalities. The objectives of the current article were to assess the impact of climate change on cardiovascular health and to propose specific interventions to mitigate the impact of these changes on cardiovascular health. Climate change significantly increases the risk of multiple cardiovascular events resulting in impairment of quality of life and deaths. Acknowledging the magnitude of CVDs and the role of climate change in the exacerbation of the diseases, there is an immense need to integrate climate resilience into public health policies, including urban planning, housing, and heat mitigation strategies. In conclusion, climate change has significantly contributed to the rising magnitude of CVDs. The need of the hour is to implement targeted interventions to reduce the impact of climate change on cardiovascular risks and minimize suffering.